P99 Pulmonary Rehabilitation in Interstitial Lung Disease Patients: Effects on Maximum Exercise Capacity, Anxiety and Depression. (19th November 2012) - Peasey, MM; Kon, SS; Dilaver, D; Canavan, JL; Ng, MG; Jones, SE; Clark, AL; Polkey, MI; Man, WD-C
Abstract : Background: There is increasing evidence to support the use of Pulmonary Rehabilitation (PR) in patients with Interstitial Lung Disease (ILD). Several studies have shown significant improvements in six minute walk distance and health related quality of life measures, such as the Chronic Respiratory Disease Questionnaire (CRQ), following PR (Holland et al; 2008) . However there is a paucity of data surrounding other outcome measures such as maximal walking exercise tests (the incremental shuttle walk: ISW) or anxiety and depression levels. As the ISW and the Hospital Anxiety and Depression scale (HAD) are commonly used outcome measures in UK PR programmes, the aim of the study was to assess the response of these outcomes to PR in the ILD population. Methods: We analysed outcome data in 62 (30 male:32 female) consecutive ILD patients completing an 8-week outpatient PR programme. Diagnoses were idiopathic pulmonary fibrosis (n=29), connective tissue related ILD (n=8), sarcoidosis (n=14), hypersensitivity pneumonitis (n=3), asbestosis (n=4), drug induced ILD (n=4). Pre- and post-PR data was analysed using either Paired T-Tests or Wilcoxon Tests. Results: Baseline mean (standard deviation) age was 70(11) years, FVC 69 (22)% predicted and median (25th, 75th centiles) MRC dyspnoea score was 4 (3, 4). There was a significant improvement in ISW (95% confidence intervals 31, 69 metres), HAD-Anxiety (95% CI –0.8, –2.4) and HAD-Depression (95% CI –0.7, –2.3). There were also significant improvements in all domains of the CRQ. Conclusion: The ISW and HAD scores are responsive to PR in patients with ILD.